Feng-Liu's Type Fixed Point Theorem in Modular Function Spaces - Asif, Mehreen; Kamran, Tayyab; Ishtiaq, Umar; Popa, Ioan-Lucian (Contemporary Mathematics, 2025)
We establish a Feng-Liu's type fixed point theorem within the framework of modular function spaces. Using this result, we investigate the existence of solutions to a Volterra-type integral inclusion in modular function spaces. The generalized setting enables us to handle multivalued mappings and broader classes of integral inclusions, thus extending classical fixed point theorems to a more flexible analytical environment.